Adult ADHD as a risk factor for dementia: integrating longitudinal evidence, mechanistic insights, and the role of stimulant treatment - Golimstok, Angel; Berrios, Waleska (Frontiers in Dementia, 2025)
Adult attention-deficit/hyperactivity disorder (ADHD) is increasingly recognized as a persistent neurodevelopmental condition with long-term implications for cognitive aging and dementia risk. Epidemiological and longitudinal studies indicate that adults with ADHD have a higher incidence of non-amnestic dementia subtypes, including Lewy body disease, and may be particularly susceptible to age-related cognitive decline. Convergent mechanistic evidence implicates dopaminergic dysregulation, possible Wnt/mTOR pathway alterations, oxidative stress, and chronic neuroinflammation as shared biological pathways linking ADHD to neurodegeneration. Psychiatric comorbidities, lifestyle factors, and reduced cognitive reserve may further amplify vulnerability, decreasing the brain’s resilience to neuropathological insults. Preliminary data suggest that stimulant treatments, such as methylphenidate and amphetamine derivatives, may attenuate dementia risk by normalizing dopaminergic tone, enhancing cortical plasticity, and reducing oxidative stress, although randomized trials are needed to confirm these protective effects. Emerging biomarker and genetic studies, including polygenic ADHD risk scores, α-synuclein, amyloid/tau, and GBA mutations, offer opportunities for early detection, risk stratification, and mechanistic insights. Integrating epidemiological, neuroimaging, molecular, and pharmacological data could guide targeted preventive interventions, highlighting ADHD as a developmental and potentially modifiable risk factor for late-life neurodegenerative disorders.